2021
DOI: 10.3390/nu13113991
|View full text |Cite
|
Sign up to set email alerts
|

Nannochloropsis oceanica as a Microalgal Food Intervention in Diet-Induced Metabolic Syndrome in Rats

Abstract: The microalgal genus Nannochloropsis has broad applicability to produce biofuels, animal feed supplements and other value-added products including proteins, carotenoids and lipids. This study investigated a potential role of N. oceanica in the reversal of metabolic syndrome. Male Wistar rats (n = 48) were divided into four groups in a 16-week protocol. Two groups were fed either corn starch or high-carbohydrate, high-fat diets (C and H, respectively) for the full 16 weeks. The other two groups received C and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…A comprehensive utilization of microalgae could significantly reduce the cost of microalgae biofuels, which included microalgae cultivation using wastewaters in outdoor raceway ponds (Arora et al, 2016;Gao et al, 2018;Keerthana et al, 2020) and the production of bioactive substances such as polysaccharides (Li et al, 2019), antiviral substances (Fritzsche et al, 2021), bioactive peptides (Donadio et al, 2021), and carotenoids (du Preez et al, 2021;Todorovićet al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive utilization of microalgae could significantly reduce the cost of microalgae biofuels, which included microalgae cultivation using wastewaters in outdoor raceway ponds (Arora et al, 2016;Gao et al, 2018;Keerthana et al, 2020) and the production of bioactive substances such as polysaccharides (Li et al, 2019), antiviral substances (Fritzsche et al, 2021), bioactive peptides (Donadio et al, 2021), and carotenoids (du Preez et al, 2021;Todorovićet al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that supplementation with Clostridium butyricum in diabetic mice could reduce systemic insulin resistance and inflammation, increase mitochondrial metabolism, and significantly reduce gut damage [ 466 ]. Besides, N. oceanica has applicability to produce biofuels and it was also reported to improve the abundance of Oxyphotobacteria in order to treat metabolic syndrome [ 461 ]. Lactobacillus plantarum strain Ln4 administration changes the expression of several hepatic genes (increased mRNA levels of IRS2, Akt2, and AMPK and reduced CD36) that regulate glucose and lipid metabolism [ 465 ].…”
Section: Promising Therapy Of Targeting the Gut Microbiota In Cvdsmentioning
confidence: 99%
“…The Tisochrysis lutea treatment also reduced the adipose tissue mass, blood leptin and TNF-α levels, and TAG and cholesterol contents in the liver, without any change in the blood IL-6, IL-4, and LPS concentrations. The expression level of IL-10 in the abdominal fat tissue was increased [ 77 ]. Preez et al, reported similar results of Sargassum siliquosum treatment and they found that it reduced abdominal fat deposition and liver fat droplet sizes [ 78 ].…”
Section: Treating Metabolic Diseasesmentioning
confidence: 99%